Language diversity and inclusion in humanitarian organisations: Mapping an NGO’s language capacity and identifying linguistic challenges and solutions - Tesseur, Wine; O'Brien, Sharon; Friel, Enida (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
This article examines whether language diversity among staff in humanitarian organisations may affect inclusion and, if so, in what ways it does. We draw on the findings of a survey on staff’s language skills in the international NGO GOAL. We also draw parallels with practices noted in other international NGOs in previous research. Prior to the survey, data were lacking on the languages GOAL works in, which staff work multilingually, and whether gaps existed in language capacity and translation provision. The data provide evidence of the rich multilingual landscape in GOAL and reveal some patterns in the language use and multilingualism of staff. The survey investigates the notion that inclusion also has a linguistic dimension: staff and local communities speak a variety of languages, yet the main working language of the international humanitarian sector is English and, by extension, a handful of other major former colonial languages such as French and Spanish. Data-gathering such as that done in this study is important for two main reasons: without such data, INGOs cannot fully understand the level of exclusion that some of their staff may be facing because of language differences; and they are unable to grasp the extent to which they rely on the multilingual skills of their staff to provide ad hoc translation solutions that ensure effective communication and successful humanitarian assistance. The article aims to advance the debate on language challenges in the NGO sector by offering concrete data on informal translation and interpreting practices in one example that is representative of language practices in the international humanitarian sector. This contribution will hopefully encourage other international NGOs to collect similar data on language use and barriers that will help organisations to deal positively with the linguistic dimension of inclusiveness.